Локально-регіональні рівні вітчизняного наративу - Верменич, Я.В. (Український історичний журнал, 2013)
Критичному аналізу піддається вітчизняне бачення ґранд-наративу як простеження у «великому форматі» основних етапів еволюції – від появи на території
сучасної України осілого населення до сьогодення. Як альтернатива пропонується
локально-регіональна схема історичної репрезентації з акцентом на перехресних культурних впливах. In this work to the critical review subjected the domestic view of the grand-narrative
as the tracing in the «big format» of the main stages of the evolution – all the way
from appearance of settled population on the territory of modern Ukraine to nowadays.
Author proposes the local-regional scheme of historical representation with the accent
on the crossed cultural influences as the alternative.